Oil and Blood in the Orient, Redux - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2017)
This research note updates selected charts from three previous papers. The new data present a rather startling picture, suggesting that the Middle East – and the global political economy more generally – might face an important crossroads. Our assessment here rests on the analysis of capital as power, or CasP. Beginning in the late 1980s, we suggested that, since the late 1960s, the Middle East was greatly influenced by the capitalized power of a Weapondollar-Petrodollar Coalition – a loose coalition comprising the leading oil companies, the OPEC cartel, armament contractors, engineering firms and large financial institutions – whose differential accumulation benefitted from and in turn helped fuel and sustain Middle East `energy conflicts'. These conflicts, we argued, reverberated far beyond the region: they affected the ups and downs of global growth, the gyrations of inflation and, in some important respects, the very evolution of the capitalist mode of power. And this impact, it seems to us, is now being called into question.
Keywords: 330; conflict; differential accumulation; energy; Middle East